2019
DOI: 10.1111/zsc.12400
|View full text |Cite
|
Sign up to set email alerts
|

Unrecognized diversity of a scale worm, Polyeunoa laevis (Annelida: Polynoidae), that feeds on soft coral

Abstract: A goal of taxonomy is to employ a method of classification based on phylogeny that captures the morphological and genetic diversity of organismal lineages. However, morphological and genetic diversity may not always be concordant, leading to challenges in systematics. The scale worm Polyeunoa laevis has been hypothesized to represent a species complex based on morphology, although there is little knowledge of its genetic diversity. Commonly found in Antarctic waters and usually associated with gorgonian corals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…We find conserved gene orders in scale worms from both anchialine caves and the midwater despite both habitats subjecting inhabitants to strong environmentally driven selective pressure, as shown by their behavioural shifts and morphological transformations (Fig. 3 a–d) 36 – 39 . Zhang et al 25 found significant differences between shallow- and deep-living polynoids, indicating purifying selection.…”
Section: Discussionmentioning
confidence: 90%
“…We find conserved gene orders in scale worms from both anchialine caves and the midwater despite both habitats subjecting inhabitants to strong environmentally driven selective pressure, as shown by their behavioural shifts and morphological transformations (Fig. 3 a–d) 36 – 39 . Zhang et al 25 found significant differences between shallow- and deep-living polynoids, indicating purifying selection.…”
Section: Discussionmentioning
confidence: 90%
“…Polyeunoa laevis was obtained from various localities, including Adélie Land, Peninsula and Ross Sea continental regions, as well as from Kerguelen. Sequences from the Amundsen Sea, Argentinean seamounts, Indian Ocean, and New Zealand (Brasier et al, 2017 ; Bogantes et al, 2020 ; Serpetti et al, 2017 ; Schiaparelli unpublished, see Table A2 ) were also added to this analysis. The length of the alignment was 658‐bp, of which 103 sites were phylogenetically informative.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, cluster 2 identifies shared haplotypes between the Kerguelen archipelago and Argentinean seamounts, suggesting a possible transport of this lineage from east toward Kerguelen, following the APF. Tracing the complex history of P. laevis outside the Antarctic continent will require additional sequences from seamounts south and north of the APF, particularly near South America and other sub‐Antarctic archipelagos such as Prince Edward Island where the P. laevis holotype has been described (Bogantes et al, 2020 ). Southern Indian Ocean sequences provided by (Serpetti et al, 2017 ) have helped to reveal a group of haplotypes shared with samples from Kerguelen and uncovered two other genetically distinct individuals separated by 9 mutational steps (cluster 2, Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, DNA barcoding of 16 Antarctic polychete morphospecies found evidence of cryptic diversity in over half the morphospecies examined, including taxa identified in the present study, such as Aglaophamus trissophyllus and Maldane sarsi (Brasier et al, 2016), suggesting that assessment based on morphology alone may significantly underestimate true species diversity. More recently, evidence of cryptic diversity has been found in Southern Ocean lineages of the polynoid Polyeunoa laevis (Bogantes et al, 2020), a taxon also present in the JR17003a samples.…”
Section: Morphological Limitations and Future Molecular Workmentioning
confidence: 97%